2013
DOI: 10.1371/journal.pone.0068385
|View full text |Cite
|
Sign up to set email alerts
|

The miRNA Pathway Controls Rapid Changes in Activity-Dependent Synaptic Structure at the Drosophila melanogaster Neuromuscular Junction

Abstract: It is widely accepted that long-term changes in synapse structure and function are mediated by rapid activity-dependent gene transcription and new protein synthesis. A growing amount of evidence suggests that the microRNA (miRNA) pathway plays an important role in coordinating these processes. Despite recent advances in this field, there remains a critical need to identify specific activity-regulated miRNAs as well as their key messenger RNA (mRNA) targets. To address these questions, we used the larval Drosop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 71 publications
(130 reference statements)
3
44
0
1
Order By: Relevance
“…mir-8 is postsynaptic and regulates levels of the effector protein Enabled (Ena), an actin regulator (Loya et al 2009(Loya et al , 2014. mir-8 was also identified in a screen for miRNAs that are differentially regulated by activity (Nesler et al 2013). This same study demonstrated that mir-8 regulates wg expression in vitro, supporting a role for mir-8 in synaptic plasticity.…”
Section: Mechanisms Regulating Growth and Plasticitymentioning
confidence: 77%
“…mir-8 is postsynaptic and regulates levels of the effector protein Enabled (Ena), an actin regulator (Loya et al 2009(Loya et al , 2014. mir-8 was also identified in a screen for miRNAs that are differentially regulated by activity (Nesler et al 2013). This same study demonstrated that mir-8 regulates wg expression in vitro, supporting a role for mir-8 in synaptic plasticity.…”
Section: Mechanisms Regulating Growth and Plasticitymentioning
confidence: 77%
“…Similarly, we have shown that spaced stimulation rapidly downregulates levels of five miRNAs in Drosophila larval ventral ganglia (Nesler et al, 2013). We demonstrated that three of these miRNAs (miRs-8, -289, and -958) control rapid presynaptic bouton growth at the larval NMJ.…”
Section: Introductionmentioning
confidence: 76%
“…Stocks were obtained from the following sources: Canton-S, w 1118 (Iso31), UAS-CamKII Ala , UAS-CamKII R3(WT) , UAS-CamKII T287A , UAS-CamKII T287D , and C380-Gal4 (Bloomington Drosophila Stock Center); UAS-CamKII v38930 and UAS-CamKII v47280 long hairpin RNAi lines (Vienna Drosophila Resource Center) (Dietzl et al, 2007); UAS-CamKII:EYFP-CamKII 3’UTR and UAS-CamKII:EYFP-NUT 3’UTR were gifts from S. Kunes (Ashraf et al, 2006); UAS-mCherry: miR-289 pri-miRNA was from Barbee lab stocks (Nesler et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations